Previous exposure to musical auditory stimulation immediately influences the cardiac autonomic responses to the postural change maneuver in women - Castro, Bianca C. R. de [UNESP]; Guida, Heraldo Lorena [UNESP]; Roque, Adriano L; Abreu, Luiz Carlos de; Ferreira, Lucas Lima; Raimundo, Rodrigo D.; Monteiro, Carlos B. M.; Goulart, Flávia Cristina; Ferreira, Celso; Ribiero, Vivian F.; Vanderlei, Luiz Carlos M. [UNESP]; Marcomini, Renata S. [UNESP]; et al. (My University, 2013)
Background: Chronic exposure to musical auditory stimulation has been reported to improve cardiac autonomic regulation. However, it is not clear if music acutely influences it in response to autonomic tests. We evaluated the acute effects of music on heart rate variability (HRV) responses to the postural change maneuver (PCM) in women. Method: We evaluated 12 healthy women between 18 and 28 years old and HRV was analyzed in the time (SDNN, RMSSD, NN50 and pNN50) and frequency (LF, HF and LF/HF ratio) domains. In the control protocol, the women remained at seated rest for 10 minutes and quickly stood up within three seconds and remained standing still for 15 minutes. In the music protocol, the women remained at seated rest for 10 minutes, were exposed to music for 10 minutes and quickly stood up within three seconds and remained standing still for 15 minutes. HRV was recorded at the following time: rest, music (music protocol) 0–5, 5–10 and 10–15 min during standing. Results: In the control protocol the SDNN, RMSSD and pNN50 indexes were reduced at 10–15 minutes after the volunteers stood up, while the LF (nu) index was increased at the same moment compared to seated rest. In the protocol with music, the indexes were not different from control but the RMSSD, pNN50 and LF (nu) were different from the music period. Conclusion: Musical auditory stimulation attenuates the cardiac autonomic responses to the PCM.
Keywords: música; estímulo auditivo; fisiologia; sistema nervoso autônomo; audição